Determining Subuh Prayer Time Using GNU Octave To Find Polynomial Roots - Damanhuri, Adi; Maskufa; Hadi, Chairul (Program Studi Ilmu Falak UIN Sunan Ampel Surabaya, 2022)
The standard used for the dawn prayer time schedule by the Indonesian government is the sun elevation angle 20°. That standard has been corrected a lot because it has not been assumed too late. Early research at dawn is mostly done using simple photometry tools, namely SQM, the processing of SQM output data varies, one of which is by polynomials, by reducing its function to the second derivative, and the first derivative root is substituted into the second derivative, so the turning point solution is represented by ?2y/?2t <0. The GNU Octave application helps to find the root of the first derivative easier and simpler by writing commands so that the root of the first derivative is obtained. With the polynomial method using GNU Octave, analyzing 19 observational data shows that the lowest elevation angle is -21.53 °, which means 1.53 ° faster, or 6 minutes 7.2 seconds from the official schedule, and the highest elevation angle is -11.38 ° or 34 minutes 28.8 seconds slower. On an average the elevation of the Sun angle is -16.59 ° ± 2.82 ° with difference of 3.41 ° or 13 minutes 38.4 seconds from the official schedule.